2020
DOI: 10.1111/jfpp.14932
|View full text |Cite
|
Sign up to set email alerts
|

The potential of pulsed light treatment to produce enzymatically stable Indian gooseberry (Emblica officinalisGaertn.) juice with maximal retention in total phenolics and vitamin C

Abstract: Indian gooseberry (Emblica officinalis Gaertn.), also known as amla, is considered as a valuable fruit due to the vast content of polyphenols, tannins, minerals, and other phytochemicals. The antioxidant activity of this fruit is due to the presence of emblicanin A and B, which mainly include glucose, gallic, and ellagic acids (Chinprahast, Siripatrawan, Leerahawong, & Traiananwuttikul, 2013). Besides, it is the most abundant source of vitamin C within the citrus fruit family except Barbados cherry, and depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 28 publications
(70 reference statements)
6
39
0
Order By: Relevance
“…The near‐IR domain of the PL spectrum is responsible for the heating of the treated sample (Demirci & Krishnamurthy, 2011). An extended PL exposure increases the possibility of overheating in the sample (Chakraborty et al., 2020; Yang et al., 2011). The instantaneous high energy during PLT is eventually converted into heat, and the inside content of the cell is emptied via explosion and evacuation.…”
Section: Overview Of Pl Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The near‐IR domain of the PL spectrum is responsible for the heating of the treated sample (Demirci & Krishnamurthy, 2011). An extended PL exposure increases the possibility of overheating in the sample (Chakraborty et al., 2020; Yang et al., 2011). The instantaneous high energy during PLT is eventually converted into heat, and the inside content of the cell is emptied via explosion and evacuation.…”
Section: Overview Of Pl Treatmentmentioning
confidence: 99%
“…Interestingly, the bromelain activity in the juice, which is beneficial for consumer health (as it helps in protein digestion), remained unchanged by PLT. However, in Indian gooseberry juice, PPO and POD were completely inactivated when the intensity was 3012 J·cm –2 (Chakraborty et al., 2020). On the other hand, the stimulation of phenylalanine ammonia lyase (PAL) can lead to an increased content of phenolic compounds.…”
Section: Impact Of Pl On Various Attributes Of Fruit Juicementioning
confidence: 99%
“…The impact of pulsed light (PL) treatment conditions on the Vitamin C content in Indian gooseberry (amla) juice was explored, and the results showed that a 61% better retention was obtained in comparison to the thermally pasteurised counterpart [80]. Similarly, the positive effect of the ozone treatment when compared to traditional pasteurisation was shown by Sroy et al 2019 [81], who studied Vitamin C behaviour in cantaloupe melon juice immediately after treatment but, also, during refrigerated storage.…”
Section: Effect Of Nonthermal Processes On Vitamin C Retentionmentioning
confidence: 99%
“…Indian gooseberry juice (Chakraborty et al, 2020) Gooseberry juice was evaluated directly after the treatment: 1. Untreated 2.…”
Section: Product (References) Treatment Applied Color Changes Natural Pigments Changesmentioning
confidence: 99%
“…Such results indicate that browning of apple fresh cuts may be caused not only by direct photodegradation of phenolics but also by cellular structure decomposition and enhancement of substrate–enzyme interactions or modification of enzymatic activity. The modification of enzyme activity as a result of PL treatment can be also one of the factors that influence the color and phenolic content in Indian gooseberry juices (Chakraborty et al., 2020). Because juices are food systems with totally disintegrated cellular structure, no degradation of vacuoles or other cell organelles can happen.…”
Section: Effect Of Nonthermal Treatment On Natural Food Pigments and ...mentioning
confidence: 99%